Compliance Analysis of Mask Wear Obligation Policy for Community as Prevention of Covid-19 Transmission in Banyumas Regency - Arif Kurniawan; Yuditha Nindya; Arrum Firda Ayu Maqfiroch (Insights in Public Health Journal, 2022)
Background: The Banyumas Regency Government issued Regional Regulation Number 2, 2020 concerning the prevention and management of diseases in Banyumas Regency, which was implemented on April 21, 2020, especially the obligation to wear masks. However, in Banyumas Regency, community compliance in applying masks when outside the home tends to be low. This study aims to determine the factors that affect compliance with the obligation to use masks in communities outside the home in Banyumas Regency to prevent transmission of COVID-19. Methods: This study used quantitative methods with cross sectional approach. Results: The results showed the level of compliance with wearing masks in the Covid-19 pandemic era had a high level of adherence 60.5%. The factors that influence community compliance with the obligation to use masks outside the house in Banyumas Regency are attitude (p-value 0.001) and personality (p-value 0.003). Meanwhile, environmental factors (p-value 0.003), referral power (p-value 0.003), force encouragement (p-value 0.003) and supervision support (p-value 0.003) have no effect on people's compliance with using masks when outside the home. Conclusion: The government needs to increase repressive / corrective disciplinary measures that are stricter on violations of compliance with wearing masks that are consistent with the Regional Regulation that has been made. Intervention with the community is also needed to increase public understanding of the benefits of preventing the transmission of Covid 19 and how to use mask correctly.